The manager's pocket calculator : a quick guide to essential business formulas and ratios - Thomsett, Michael C. (American Management Association, 2011)
"The Manager's Pocket Calculator" gives readers the essentials of budgeting and forecasting, financial analysis, reporting, interest and rate-of-return calculation, statistics, and more. Not just an overview, the book contains more than 100 formulas and ratios with numerical examples, spreadsheet entries, and step-by-step calculations